Cell cycle control of spindle elongation - Roostalu, Johanna; Schiebel, Elmar; Khmelinskii, Anton (Cell cycle, 2010)
Different organisms employ a variety of strategies to segregate their chromosomes during mitosis. Despite these differences, however, the basic regulatory principles that govern this intricate process are evolutionarily conserved. Above all, rapid dephosphorylation of mitotic phosphoproteins upon the metaphase-to-anaphase transition has proven to be essential for proper function of the mitotic spindle and accurate chromosome segregation in all eukaryotes. Recently, a central midzone component, the microtubule crosslinker Ase1/PRC1 (anaphase spindle elongation 1/protein regulating cytokinesis 1), was uncovered as a universal target of such control mechanism. Depending on its phosphorylation status, Ase1 either restrains spindle elongation in metaphase or promotes it after anaphase onset via recruitment of kinesin motor proteins to the midzone. Here we discuss the potential role of Ase1/PRC1 as a central regulatory platform that interconnects distinct functions of the midzone such as spindle stability, spindle elongation and cytokinesis. Additionally, we provide a comparative overview of the chromosome segregation strategies used by the main model organisms.
Gesehen am 16.06.2023